(untitled) (Bangladesh Journal of Neuroscience, 2026)
Cerebral toxoplasmosis is an opportunistic infection of brain caused by Toxoplasma gondii, which is a zoonotic intra-cellular parasite transmitted from cat and other feline animals. In immunocompetent person it causes mainly asymptomatic infection. But in case of immunocompromised people, reactivation of dormant organisms causes widespread dissemination producing focal or global cerebral symptoms. CD4+ lymphocytes provide the main defense against toxoplasmosis. So, in case of AIDS when CD4+ cell count falls below a critical level, predisposition to cerebral toxoplasmosis occurs giving it the title of an AIDS defining illness.